Information Sharing and Information Acquisition in Credit Markets - Artashes Karapetyan; Bogdan Stacescu (Norges Bank, 2010)
Since information asymmetries have been identified as an important source of bank profits, it may seem that the establishment of information sharing (e.g., introducing credit bureaus or public registers) will lead to lower investment in acquiring information. However, banks base their decisions on both hard and soft information, and it is only the former type of data that can be communicated credibly. We show that when hard information is shared, banks will invest more in soft information. These will produce more accurate lending decisions, provide higher welfare, lead to an increased focus on relationship banking and favor informationally opaque borrowers. We test our theory using a large sample of firm-level data from 24 countries.
hdl:11250/2497437
Keywords: G21; L13; 330; bank competition; information sharing; relationship bank; hard; soft